Financial Performance Analysis Based on Liquidity and Profitability Ratios - Nisrina, Ulfah Laila; Yusuf, St. Nursaadah; Aliyah, Nur (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study examines the company's performance based on profitability and liquidity ratios at CV Alfaiz Putra Mandiri. CV Alfaiz Putra Mandiri is a trading company that sells furniture materials, namely HPL (High Pressure Laminated). This study aims to analyze financial performance based on liquidity and profitability ratios at CV Alfaiz Putra Mandiri. The method used is quantitative method. The type of research used is field and library research by applying document analysis data collection techniques and interviews. Based on the analysis of the liquidity ratio of CV Alfaiz Putra Mandiri, the company's financial performance is quite good. This is due to the increase in current assets from year to year. However, current debt has also increased from year to year which offsets the increase in current assets. Based on the profitability ratio analysis, the company's financial performance is not good enough. This is because the increase in sales is not matched by the increase in profits generated and there are still many costs incurred for the company's operational needs so as not to generate optimal profits